2017
DOI: 10.1097/md.0000000000009203
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-13 +2044 G/A and +1923C/T polymorphisms are associated with asthma susceptibility in Asians

Abstract: A number of studies have reported that the interleukin 13 (IL-13) gene is associated with asthma susceptibility. However, the reported relationships between the +2044G/A and +1923C/T polymorphisms and asthma susceptibility are inconsistent, especially in Asian adults and children with atopic status. Meta-analysis was used to analyze combined data.The +2044G/A and +1923C/T polymorphisms were investigated using data from 18 and 11 studies, respectively. The results suggested that there was an association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
4
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
(42 reference statements)
2
4
4
1
Order By: Relevance
“…In line with these findings, we presume IL-13 +2044 A/G and IL-4 -590 C/T polymorphisms maybe potential susceptible predictor for pediatric asthma. However, some studies showed that IL-13 -1112C/T and +1923C/T polymorphisms were correlated with increased risk of asthma in children, [ 68 , 69 , 71 ] which is different from our results. The reasons may be as follows: on the one hand, a significantly increased risk between IL-13 -1112C/T and asthma risk was observed by Liu et al [ 68 ] in overall populations, but not in Asians or Chinese.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In line with these findings, we presume IL-13 +2044 A/G and IL-4 -590 C/T polymorphisms maybe potential susceptible predictor for pediatric asthma. However, some studies showed that IL-13 -1112C/T and +1923C/T polymorphisms were correlated with increased risk of asthma in children, [ 68 , 69 , 71 ] which is different from our results. The reasons may be as follows: on the one hand, a significantly increased risk between IL-13 -1112C/T and asthma risk was observed by Liu et al [ 68 ] in overall populations, but not in Asians or Chinese.…”
Section: Discussioncontrasting
confidence: 99%
“…[ 67 ] Our results demonstrated that IL-13 +2044G/A and IL-4 -590C/T polymorphisms were associated with asthma risk in total populations and Chinese, while IL-13 -1112C/T, +1923C/T polymorphisms were not associated with the risk of childhood asthma in any models. These results are partially consistent with the previous meta-analyses: Liu et al [ 68 ] and Mei and Qu [ 69 ] found that IL-13 +2044A/G polymorphism was significantly associated with asthma risk in Asian children; Zhang et al [ 70 ] found that a strong association between the IL-4 - 590 C/T polymorphism and the risk of childhood asthma; a meta-analysis showed that IL-4 -590 C/T polymorphism was associated with asthma risk among Chinese children. In line with these findings, we presume IL-13 +2044 A/G and IL-4 -590 C/T polymorphisms maybe potential susceptible predictor for pediatric asthma.…”
Section: Discussionsupporting
confidence: 93%
“…In line with these ndings, we presume IL-13 + 2044 A/G and IL-4 -590 C/ T polymorphism maybe risk factors in pediatric asthma. However, some studies has shown that IL-13 -1112C/T and IL-13 + 1923C/T variant were correlated with increased risk of asthma in children 58,59,61 , which is different from our results. The reasons may be the following: a signi cantly increased risk between IL-13 -1112C/T and asthma risk was observed by Liu et al 58 in overall populations, but not in Asians.…”
Section: Sensitivity Analysis and Publication Biascontrasting
confidence: 99%
“…Our results demonstrated that IL-13 + 2044G/A and IL-4 -590C/T polymorphism were associated with asthma risk in total populations and Asians, IL-13 -1112C/T and IL-13 + 1923C/T polymorphism were not associated with the risk of childhood asthma in any of the models. These results are partially consistent with the previous meta-analyses : Liu et al 58 and Mei et al 59 found that IL-13 + 2044A/G polymorphism was signi cantly associated with asthma risk in Asian children; Zhang et al 60 found that a strong association between the IL-4 -590 C/ T polymorphism and the risk of childhood asthma; a meta-analysis showed that IL-4 -590 C/ T polymorphism was associated with asthma risk among Chinese children. In line with these ndings, we presume IL-13 + 2044 A/G and IL-4 -590 C/ T polymorphism maybe risk factors in pediatric asthma.…”
Section: Sensitivity Analysis and Publication Biassupporting
confidence: 93%
“…Numerous genetic and molecular studies have been carried out in the eld of asthma in both the children and in adults previously [50][51][52][53][54][55][56][57][58][59][60]. Among genetic studies, exome/NG sequencing studies has been documented throughout the global populations [61,62].…”
Section: Resultsmentioning
confidence: 99%